Anleitungen rezipieren, Anleitungen produzieren: Empirische Befunde zu kognitiven Prozessen bei Übersetzungsnovizen und Übersetzungsproﬁs - Göpferich, Susanne (HERMES - Journal of Language and Communication in Business, 2010)
The article presents results from the research project TransComp, a process-oriented longitudinal study which investigates the development of translation competence in 12 students of translation over a period of three years and compares it with that of 10 professional translators. The article focuses on the translation products and processes of six novices and ﬁve professional translators who had to translate operating instructions from English (their L2) into German (their L1). During the translation process, the participants had to think aloud. They were allowed to use any external reference resources they wished. Their think-aloud and all their activities on the computer were screen-recorded using CamtasiaStudio. In addition, their writing processes were logged using the keystroke-logging software Translog. Immediately after the experiments, they were asked to complete a questionnaire. The data gained in this multi-method approach are analyzed both from a product-oriented and from a process-oriented perspective. For the product-oriented analyses, an error classiﬁcation was developed that combines a linguistic characterization of the mistakes with a functional approach of determining how detrimental these are with regard to the target text function. The process-oriented analyses are based on the subjects’ think-aloud, their activities recorded with CamtasiaStudio, their questionnaires and their log ﬁles. These process data are analyzed to determine the subjects’ problem awareness and their problem-solving competence. Based on the ﬁndings, implications for translation pedagogy and text production didactics are discussed.